Dyadic differences in empathy scores are associated with kinematic similarity during conversational question-answer pairs - Trujillo, James P.; Dyer, Rebecca M. K.; Holler, Judith (Discourse processes, 2025)
During conversation, speakers coordinate and synergize their behaviors at multiple levels, and in different ways. The extent to which individuals converge or diverge in their behaviors during interaction may relate to interpersonal differences relevant to social interaction, such as empathy as measured by the empathy quotient (EQ). An association between interpersonal difference in empathy and interpersonal entrainment could help to throw light on how interlocutor characteristics influence interpersonal entrainment. We investigated this possibility in a corpus of unconstrained conversation between dyads. We used dynamic time warping to quantify entrainment between interlocutors of head motion, hand motion, and maximum speech f0 during question-response sequences. We additionally calculated interlocutor differences in EQ scores. We found that, for both head and hand motion, greater difference in EQ was associated with higher entrainment. Thus, we consider that people who are dissimilar in EQ may need to "ground" their interaction with low-level movement entrainment. There was no significant relationship between f0 entrainment and EQ score differences.